PENGARUH MODEL PEMBELAJARAN TAI (TEAM ASSISTED INDIVIDUALIZATION) TERHADAP HASIL BELAJAR SISWA - Moh. Halih (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2016)
The research was done because there were a lot of students who have minimum score in mathematic subject. The statement of the problem is “Is there any influence in TAI teaching model to the students’ achievement?”. The purpose of this study is to know the influence of TAI teaching model to the students’ mathematic achievement. TAI teaching model is one of the model in teaching which focuses on group, the students were divided in some small group in a class, member of group were consists of 4-5 students in a group. Then in this research the students were given “Himpunan”material.The sample of this research consists of two classes, the first is experiment class with 33 students who were given TAI teaching model, then the second is control class with 33 students who were given conventional teaching model. To know and analyze the students’ achievements, the researcher used posttest for both two classes. Based on the research conducted at SMP Rahmat Surabaya. The researcher concluded that the result of using TAI teaching model was given significant change the students score of experiment class, than using conventional teaching model in control class. After the students are given “Himpunan” material, they are given a posttest for the data analysis. The writer uses t-test for the data analysis. The research result is tcount<ttable (). So it could be conclude that TAI teaching model influenced on the students’ mathematic achievement for the seventh grade students on SMP Rahmat Surabaya. Keywords: TAI teaching model, students’ achievement.